Varicella Virus-Host Interactions During Latency and Reactivation: Lessons From Simian Varicella Virus - Sorel, Océane; Messaoudi, Ilhem (Frontiers in Microbiology, 2018)
Varicella zoster virus (VZV) is a neurotropic alphaherpesvirus and the causative agent of varicella (chickenpox) in humans. Following primary infection, VZV establishes latency in the sensory ganglia and can reactivate to cause herpes zoster, more commonly known as shingles, which causes significant morbidity and sometimes mortality in the elderly. Because VZV infection is highly restricted to humans, the development of a reliable animal model has been challenging and our understanding of VZV pathogenesis remains incomplete. As an alternative, infection of rhesus macaques with the homologous simian varicella virus (SVV) recapitulates the hallmarks of VZV infection and thus constitutes a robust animal model to provide critical insights into VZV pathogenesis and the host antiviral response. In this model, SVV infection results in the development of varicella during primary infection, generation of an adaptive immune response, establishment of latency in the sensory ganglia and viral reactivation upon immune suppression. In this review, we discuss our current knowledge about host and viral factors involved in the establishment of SVV latency and reactivation as well as the important role played by T cells in SVV pathogenesis and antiviral immunity.